The functional role of hemojuvelin in acute ischemic stroke. Issue 6 (June 2020) - Young, Guang-Huar; Tang, Sung-Chun; Wu, Vin-Cent; Wang, Kuo-Chuan; Nong, Jing-Yi; Huang, Po-Yuan; Hu, Chaur-Jong; Chiou, Hung-Yi; Jeng, Jiann-Shing; Hsu, Chung Y
Our study aimed to establish the role of hemojuvelin (HJV) in acute ischemic stroke (AIS). We performed immunohistochemistry for HJV expression in human brain tissues from 10 AIS and 2 non-stroke autopsy subjects. Plasma HJV was measured in 112 AIS patients within 48 h after stroke. The results showed significantly increased HJV expression in brain tissues from AIS patients compare to non-stroke subjects. After adjusting for clinical variables, plasma levels of HJV within 48 h after stroke were an independent predictor of poor functional outcome three months post-stroke (OR:1.78, 95% CI: 1.03–3.07; P  = 0.038). In basic part, Western blotting showed that HJV expression in mice brains was apparent at 3 h after middle cerebral artery occlusion (MCAO), and increased significantly at 72 h. In cultured cortical neurons, expression of HJV protein increased remarkably 24 h after oxygen glucose deprivation (OGD), and small interfering RNAs (siHJV) transfected OGD neurons had a lower apoptotic rate. Importantly, 72 h post-MCAO, HJV knockout mice had significantly smaller infarcts and less expression of cleaved caspase-3 protein compared with wild-type mice. In summary, HJV participates in the mechanisms of post-stroke neuronal injury, and that plasma HJV levels can be a potential early outcome indicator for AIS patients.